A herpes simplex virus type 1 immediate-early gene product, IE63, regulates small nuclear ribonucleoprotein distribution. - Phelan, A (1993)
Herpes simplex virus 1 (HSV-1), a nuclear replicating DNA virus, has 73 identified genes of which only 4 contain introns. For this reason the virus probably makes only minimal use of the cellular RNA-splicing machinery. Antigens associated with the small nuclear ribonucleoprotein particles (snRNPs) that are subunits of splicing complexes have been reported to redistribute in the nucleus and become concentrated into the intranuclear structures, the interchromatin granules, after HSV-1 infection [Martin, T. E., Barghusen, S. C., Leser, G. P. & Spear, P. G. (1987) J. Cell Biol. 105, 2069-2082]. We observe this snRNP redistribution upon HSV-1 infection, in which the widespread snRNP staining pattern changes to a restricted punctate distribution with a concomitant loss of coiled bodies in HSV-1-infected cells. We show here that expression of the immediate-early (IE) subset of HSV-1 genes is necessary and sufficient for snRNP redistribution. Using a series of HSV-1 mutants in different IE genes, we have established that specifically the product of the viral IE63 (ICP27) gene is essential for this effect, and transfection experiments revealed that IE63 expression alone can cause the snRNP redistribution. Further, we show that the IE63 gene product colocalizes with the redistributed snRNP in the nucleus. The snRNP redistribution caused by HSV-1 infection resembles the effect seen after inhibition of transcription in uninfected cells. In HSV-1-infected cells, however, the snRNP redistribution is under the control of viral IE gene products and occurs during active virus gene transcription.